Baculovirus-expressed self-assembling SARS-CoV-2 nanoparticle vaccines targeting the S protein induce protective immunity in mice. (June 2023) - Liu, Xingjian; Song, Haozhi; Jiang, Jianmin; Gao, Xintao; Yi, Yongzhu; Shang, Yuting; Li, Jialei; Li, Dan; Zeng, Zhen; Li, Yinü; Zhang, Zhifang
Abstract: Spike (S) protein, a homotrimeric glycoprotein, is the most important antigen target for SARS-CoV-2 vaccines. A complete simulation of the advanced structure of this homotrimer during subunit vaccine development is the most likely method to improve its immunoprotective effects. In this study, preparation strategies for the S protein receptor-binding domain, S1 region, and ectodomain trimer nanoparticles were designed using ferritin nanoparticle self-assembly technology. The Bombyx mori baculovirus expression system was used to prepare three nanoparticle vaccines with high expression levels recorded in silkworms. The results in mice showed that the nanoparticle vaccine prepared using this strategy could induce immune responses when administered via both the subcutaneous administration and oral routes. Given the stability of these ferritin-based nanoparticle vaccines, an easy-to-use and low-cost oral immunization strategy can be employed in vaccine blind areas attributed to shortages of ultralow-temperature equipment and medical resources in underdeveloped areas. Oral vaccines are also promising candidates for limiting the spread of SARS-CoV-2 in domestic and farmed animals, especially in stray and wild animals. Graphical Abstract: ga1 Highlights: Nanoparticle Spike antigen expressed in fusion with ferritin has stronger immunogenicity. Both intramuscular and oral immunizations induce potent immune responses. Antibodies induced by nanoparticle antigens have neutralizing effect on both origin strain and delta variants of SARS-CoV-2.